The Istinbath Method of Professional Zakat Law at the Muhamadiyah Tarjih Council and Its Implications For the Implementation of Professional Zakat at the Muhammadiyah University Of North Sumatra - Ali Baroroh Al-Muflih (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
Zakat profession is a problem that has not been discussed in the time of the Prophet Muhammad. However there is no argument in the verses of the Holy Qur'an and the Prophet's Hadith explicitly explain the obligation and unobligation about the law of zakat profession. Causing the differences of opinion among Ulama about its legal status. Meanwhile in Indonesia, Islamic organizations have their respective legal provisions in establishing the law of zakat profession. In this state, Muhammadiyah through Muhammadiyah Tarjih Assembly has set the zakat profession, is a mandatory. This aim of this study is to know the law of zakat profession according to Majlis Tarjih Muhammadiyah and how the method used by Majlis Tarjih Muhammadiyah in establishing the law of zakat profession. And also the fatwa's implications about application of zakat profession at the University of Muhammadiyah North Sumatra. The method used by the writer in this research is descriptive analytical. collecting data from the literature study. This research tried to explain the istinbath method of the law of zakat profession from Muhammadiyah organization through Muhammadiyah Tarjih Assembly and fatwa implication to the law of zakat profession applied at University of Muhammadiyah North Sumatra.